Exceptional release kinetics and cytotoxic selectivity of oxidised MWCNTs double-functionalised with doxorubicin and prostate-homing peptide - Milosavljevic, Vedran; Krejcova, Ludmila; Guran, Roman; Buchtelova, Hana; Wawrzak, Dorota; Richtera, Lukas; Heger, Zbynek; Kopel, Pavel; Adam, Vojtech (Colloids and surfaces. B, Biointerfaces, 2017)
Multiwall carbon nanotubes (MWCNTs) are among the frequently studied carbon materials, particularly because of their physical and chemical properties and high potential for application in materials chemistry, industry, and medicine. MWCNTs are very promising as transporters of bioactive molecules because of their π electrons and large surface area, which can be easily modified, mostly by the application of inorganic acids for the introduction of carboxylic moieties on the surface. In the present study, we designed an oxidised MWCNTs (oMWCNTs) transporter for the targeted delivery of doxorubicin (Dox). The modification of oMWCNTs with prostate-homing peptide (SMSIARL) promotes increased cytotoxicity for prostate cancer cells. Using advanced analytical techniques, we studied the loading efficiency, stability, and release kinetics of Dox from a oMWCNTs-Dox-Pep nanoconstruct. We show that pH strictly drives Dox release, and imitating the pH of intracellular acidic compartments, 60% of Dox is released from oMWCNTs-Dox-Pep, while in plasma conditions, only a 14% release of Dox was found during 24h. The nanoconstruct displayed no cytotoxicity in non-malignant prostate cells (PNT1A), while in metastatic prostate cancer cells (LNCaP), the cytotoxic effects were close to the cytotoxicity of free Dox. This indicates that peptide modification promotes interactions with malignant cells, resulting in efficient internalisation into the intracellular region. Overall, we show that oMWCNTs are exceptional platforms for simple and stable non-covalent modification with bioactive molecules.
Keywords: Spectrometry, Mass, Matrix-Assisted Laser Desorption-Ionization; prostata; lidé; Prostate; spektrometrie hmotnostní - ionizace laserem za účasti matrice; nádorové buněčné linie; doxorubicin; mužské pohlaví; Cell Line, Tumor; nanotrubičky uhlíkové; Spectroscopy, Fourier Transform Infrared; protinádorová antibiotika; Antibiotics, Antineoplastic; Doxorubicin; spektroskopie infračervená s Fourierovou transformací; Nanotubes, Carbon; Humans; Kinetics; kinetika; Male